2021
DOI: 10.3390/ma14206146
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Conducting Polymer Applications: Methods for Achieving High Molecular Weight in Chemical Oxidative Polymerization in Alkyl- and Ether-Substituted Thiophenes

Abstract: Polythiophenes (PTs) constitute a diverse array of promising materials for conducting polymer applications. However, many of the synthetic methods to produce PTs have been optimized only for the prototypical alkyl-substituted example poly(3-hexylthiophene) (P3HT). Improvement of these methods beyond P3HT is key to enabling the widespread application of PTs. In this work, P3HT and two ether-substituted PTs poly(2-dodecyl-2H,3H-thieno[3,4-b][1,4]dioxine) (PEDOT-C12) and poly(3,4-bis(hexyloxy)thiophene) (PBHOT) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…Among them, polythiophenes emerged as well-known conducting polymers due to their remarkable stability towards oxygen and moisture, and unique optoelectronic properties that endowed them with a great potential for use as advanced materials in the development of organic thin film transistors, light emitting diodes, solar cells, supercapacitors, sensors, etc. [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polythiophenes emerged as well-known conducting polymers due to their remarkable stability towards oxygen and moisture, and unique optoelectronic properties that endowed them with a great potential for use as advanced materials in the development of organic thin film transistors, light emitting diodes, solar cells, supercapacitors, sensors, etc. [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…[22] Among these conductive polymers, ether substituents of PEDOT can reduce the oxidation potential of monomers and polymers, making them easier to polymerize and more stable during redox reactions. [23] PEDOT:PSS not only improves the solubility of PEDOT via PSS, [24] but also offers a way for tuning the radar stealth and electromagnetic interference (EMI) shielding properties through the optimization of heterogeneous interface. For example, Wang et al found that PEDOT:PSS-Fe 3 O 4 -rGO nanocomposites showed a minimum reflection loss value of -61.4 dB and a maximum bandwidth of 6.4 GHz.…”
Section: Introductionmentioning
confidence: 99%